Against Ethnicity: Democracy, Equality, and the Northern Irish Conflict. (8th November 2018) - Prince, Simon
Abstract: The study of the Northern Irish Troubles is dominated by ethnic readings of conflict and violence. Drawing on new scholarship from a range of different disciplines and on fresh archival sources, this article questions these explanations. General theories that tie together ethnicity with conflict and violence are shown to be based on definitions that fail to distinguish ethnic identities from other ones. Their claims cannot be taken as being uniquely or even disproportionately associated with ethnicity. Explanatory models specifically developed for the case of modern Ireland do address that weakness. Yet, this article contends, they rest upon the fallacy that the Catholic and Protestant peoples are transhistorical entities. Political ideas, organizations, and actions cannot be reduced to fixed group identities. This article argues instead that the Troubles centered on a political conflict—one over rival visions of modern democracy. The pursuit of equality, the core value of democracy, led not only to conflicts but also to some of those conflicts becoming violent. Focusing on Belfast in the summer and autumn of 1969, this article sets out how the main political actors asserted competing claims to popular sovereignty and traces how multiple dynamic and intersecting conflicts became arrayed around the central one.